Analysis of Methods for Extending the Life Cycle of a TP-100A Boiler - Stepan Lys; Oksana Yurasova; Nadiya Lashkovska (Energy Engineering and Control Systems)
Reconditioning of the TP-100А boiler can be implemented via a number of engineering solutions, including a complete replacement of the heating surface of the primary and secondary steam superheating circuits, boiler drum replacement, pulverized coal system closing, installation of gas-tight water walls; replacement of all the tanks of the water economizer, replacement of all the tanks of the tubular air heater (TAH); replacement of the check and control valves, replacement of all the steam pipelines in a boiler room. Closing the pulverized coal system will make it possible to avoid the discharge of the pulverized coal onto the electrostatic precipitators, thereby reducing the fuel consumption for electricity generation. Installation of gas-tight water walls provides for decreasing the cold air inflow into the furnace, which will have a positive effect on the output-input ratio and liquid slag output, while the replacement of all the heaters of the water economizer and air heater enables heating the feed water and, respectively, the cold air to the calculated value (before the reconstruction, the temperatures did not reach the calculated values). Replacement of the check and control valves provides for quality regulation of the main parameters of the steam, the pressure and temperature, with an increased speed of the power generating unit manoeuvring and reduced overburning of the fuel during the manoeuvring. In addition to the extended life cycle, the above listed operations will result in at least 2% increase in the output-input ratio of the boiler and significantly improve the manoeuvrability of the power generating unit.